Why context matters when changing the diet: A narrative review of placebo, nocebo, and psychosocial context effects and implications for outcome research and nutrition counselling - Neumann, Melanie; Wirtz, Markus Antonius; Lutz, Gabriele; Ernesti, Alina; Edelhäuser, Friedrich (Frontiers in Nutrition, 2022)
Placebo (PE) and nocebo effects (NE) have been subjects of systematic research in medicine and psychotherapy for many decades to distinguish between the (specific) pharmacological effect of medication and the (unspecific) effect of the context. Despite this significant research, the awareness, operationalization and reflection of the multiplicity of PE, NE, and psychosocial context effects (PSCE) is currently limited when researching outcomes of diet changes in studies without randomisation and placebo control. This neglection is critical as it could systematically influence outcomes by moderating and mediating them and thus reducing the validity and evidence base of these studies. Therefore, we performed a (non-systematic) narrative review (NR) on the following objectives: (1) present a concise overview about the relevance of PE, NE and PSCE in medicine and nutrition research; (2) review the current state of research on reflecting context effects when studying diet changes; (3) provide useful theoretical foundations via consideration and integration of micro- and macro context effects; (4) operationalise as hypotheses the potential PE, NE and PSCE which are specific for researching diet changes; and (5) derive their impact for future research as well as for nutrition counselling The electronic search in this NR for objective (2) identified N=5 publications and for objective (4) we found N=61 articles retrieved in the first round of search, additional references were identified by a manual and snowball search among the cited references resulting finally in N=37. This NR offers a synoptical basis to foster awareness and operationalization of a variety of PE, NE and PSCE. Interdisciplinary research teams should monitor these factors using e.g., qualitative, mixed-method studies, process evaluation, item bank approaches, moderator and mediator analysis that might reveal substantially new insights and outcomes of relevance to science and nutrition counselling. Nevertheless, the present NR has several limitations, especially as it is non-systematic, because it is a very heterogeneous field of research, in which the topic we are investigating is usually regarded as marginal and subordinate. Therefore, future research should conduct systematic reviews and particularly theory-based primary studies (experimental research) on hypotheses of PE, NE and PSCE in outcome research in diet changes.